Achieving organizational performance through knowledge management capabilities: Mediating role of organizational learning - Muhammad Kashif Imran; Muhammad Ilyas; Tehreem Fatima (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
Around the globe, transformational shift has surged to develop dynamic capabilities for better performance. One of the objectives behind these drastic swings is to readjust resources for organizational wellbeing. The grafting of updated knowledge resources within the existing capabilities is becoming the vital component to multiply the performance factor. This study conveys the pathway to performance with the help of knowledge management capabilities and organizational learning. A multi-group analysis is performed having organizational learning as mediator between knowledge management capabilities and organizational performance using Preacher and Hayes (2004) mediation analysis on 228 responses from multiple ranked employees selected at random from public and private sector banks of Pakistan. The results exhibits substantial positive influence of knowledge management capabilities on enhancing organizational performance and organizational learning partially mediates the relationship between knowledge management capabilities and organizational performance. In addition to this, public sector banks have more responsiveness to knowledge management capabilities in context with organizational performance when compared with private sector banks. These results suggest new avenues for management to attain sustained performance using knowledge management capabilities at prime level; updated technology, supportive culture, knowledge acquisition and application processes. Further, these capabilities are helpful to induce learning environment in organizations that will lead to creativity, innovation, competitive advantage and overall performance. Moreover, technology and knowledge application are factors that are crucial for both types of banks. On the other hand, culture is more decisive for public sector banks and knowledge acquisition is for private sector banks.
Keywords: 330; knowledge management capabilities; organizational performance; organizational learning; technology; culture; knowledge acquisition; knowledge application